Hooey Higgins #2: Hooey Higgins and the Tremendous Trousers - Steve Voake (Candlewick Press, 2010)
Have you ever found yourself in a slightly risky situation and thought, What I really need is a pair of super-protective trousers to keep me safe from crocodiles, flying toffee apples, and log-flume malfunctions? Head for Shrimpton-on-Sea, where Hooey, Will, and Twig are working on an ingenious contraption sure to make the world a safer place: the all-new Tremendous Trousers, aka TremTrows! All you do is slip on a pair of yellow sweatpants, stuff them full of bubble wrap, add some soda bottles topped with balloons, and inflate them with gas from a bunch of mints dropped into the soda. What could possibly go wrong? It$1 (Bs a brilliant invention guaranteed to win the class prize $1 (Btickets to the carnival! Shweet!s
Keywords: Realistic Fiction -- Realistic Fiction